Identification and characterization of a BRAF fusion oncoprotein with retained autoinhibitory domains - Weinberg, Florian; Griffin, Ricarda; Fröhlich, Martina; Heining, Christoph; Braun, Sandra Daniela; Spohr, Corinna; Iconomou, Mary; Hollek, Viola; Röring, Michael; Horak, Peter; Kreutzfeldt, Simon; Warsow, Gregor; et al. (Oncogene, 2020)
Fusion proteins involving the BRAF serine/threonine kinase occur in many cancers. The oncogenic potential of BRAF fusions has been attributed to the loss of critical N-terminal domains that mediate BRAF autoinhibition. We used whole-exome and RNA sequencing in a patient with glioblastoma multiforme to identify a rearrangement between TTYH3, encoding a membrane-resident, calcium-activated chloride channel, and BRAF intron 1, resulting in a TTYH3-BRAF fusion protein that retained all features essential for BRAF autoinhibition. Accordingly, the BRAF moiety of the fusion protein alone, which represents full-length BRAF without the amino acids encoded by exon 1 (BRAFΔE1), did not induce MEK/ERK phosphorylation or transformation. Likewise, neither the TTYH3 moiety of the fusion protein nor full-length TTYH3 provoked ERK pathway activity or transformation. In contrast, TTYH3-BRAF displayed increased MEK phosphorylation potential and transforming activity, which were caused by TTYH3-mediated tethering of near-full-length BRAF to the (endo)membrane system. Consistent with this mechanism, a synthetic approach, in which BRAFΔE1 was tethered to the membrane by fusing it to the cytoplasmic tail of CD8 also induced transformation. Furthermore, we demonstrate that TTYH3-BRAF signals largely independent of a functional RAS binding domain, but requires an intact BRAF dimer interface and activation loop phosphorylation sites. Cells expressing TTYH3-BRAF exhibited increased MEK/ERK signaling, which was blocked by clinically achievable concentrations of sorafenib, trametinib, and the paradox breaker PLX8394. These data provide the first example of a fully autoinhibited BRAF protein whose oncogenic potential is dictated by a distinct fusion partner and not by a structural change in BRAF itself.
Published: 26 September 2019
Gesehen am 18.05.2020